Correlation Between Kalachurukkam (Ritucharya) And Medicinal Plants Used in Mugapoochukkal (Muga Lepa) Mentioned in the Siddha Texts: A Literature Review - Sathiyaseelan, V.; Thillany, P.V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2018)
Siddha medicine is one of an ancient system of medicine based on ancient scientific knowledge of anatomy and chemistry other biological sciences and mainly for the quest of longevity. In the ancient society herbs played an important role in maintaining the beauty and body conditions. Many of these practices were subtly interwoven with the seasons (Kalachurukkam/Ritucharya) and the normal rituals of life (Thinachurukkam /Dhinacharya). Ancient knowledge of the healing properties of herbs also used in Mugapoochukkal (Mugalepa)/ Facial masks. Different Lepas (Masks or applications) were recommended for different seasons for body beautification. The objective of the study is to bring out the correlation between Kalachurukkam (Ritucharya) and medicinal plants used in Mugapoochukkal (Muga Lepa) which are mentioned in the Siddha texts by means of comparison with Siddha principles. In appropriately the literatures as Authenticated Siddha Texts, and for further knowledge Volumes of Astanga Hrdhayam were analyzed on the Siddha basic principles. 30 medicinal plants were used in the Mugapoochukkal (Muga Lepa) according to the Kalachurukkam (six seasons). In these Santalum album, Glycyrhizza glabra and Seasamum indicum are repetitively used in some of the seasons. According to the comparison made with the Siddha principles as high percentages of Suvai, Veeryam, Vipakam of certain medicinal plants in Ilavenil (Vasanta Ritu) is Bitter, Sheetha, Sweet and deprives Pitta, Kapha. Muthuvenil (Krishma Rudhu) have Sheetha, Sweet deprives Pitta, Kaar (Varsha Rudhu) has Sweet, Ushna, Sweet and deprives Pitta. Koothir (Sarath Rudhu) has Sweet, Ushna, Sweet and deprives Pitta. Munpani (Hemantha Rudhu) has (Bitter, Pungent, Astringent, Sweet), (Ushna, Sheetha), (Sweet, bitter) and deprives Pitta. Pinpani (Sisira Rudhu) has Sweet, Ushna, Sweet, Pungent deprives Kapha and Pitta. The gained Siddha principles of these medicinal plants relevantly relates to the dominating Tastes, provoked Dosha and mitigated Dosha. So the Medicinal plants used in each seasonal regimens were used by our ancestors with this certain prospects of Siddha. The bottom-line of the study is creating the trend toward looking back to ancient remedies in the rising demand for herbal skin care products like these Mugapoochukkal (Mugalepa) because it is becoming less and less acceptable to use facials and creams made from synthetic chemicals among the upcoming generations.
Keywords: Mugapoochukkal; Kalachurukkam; Siddha principles